Peranan Perjanjian Perkawinan yang dilakukan Sebelum Perkawinan Berlangsung Studi Komparatif Hukum Islam dan Undang-Undang Perkawinan - Rahul Maulana; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2021)
Humans as social beings created by Allah SWT as pairs cannot live alone. As creatures in pairs, humans will marry to continue their offspring. Marriage formed by humans aims to perfect their lives as social beings and also as worship. Marriage agreement is one of the basic forms of one's readiness to form a household. The marriage agreement is made by the bride and groom to achieve a harmonious relationship and avoid conflicts in the future. One form of marriage agreement that applies in Indonesia, among others, is related to Taklik Talak and also related to the arrangement of assets in marriage. Marriage agreements that exist in Indonesia are explained in Article 29 of Law Number 1 of 1974 in conjunction with Law Number 16 of 2019 concerning Marriage. Islam also emphasizes the rules for making a Marriage Agreement, as regulated in Articles 45 to 52 of the Compilation of Islamic Law. The method used in writing this research is the Normative Research Method.